Assessing the feasibility of a randomised, double-blinded, placebo-controlled trial to investigate the role of intraperitoneal ropivacaine in gastric bypass surgery: a protocol. Issue 8 (11th August 2014) - Wu, Robert; Haggar, Fatima; Porte, N'Gai; Eipe, Naveen; Raiche, Isabelle; Neville, Amy; Yelle, Jean Denis; Ramsay, Tim; Mamazza, Joseph
Abstract : Introduction: Postoperative pain control remains a major challenge for surgical procedures, including laparoscopic gastric bypass. Pain management is particularly relevant in obese patients who experience a higher number of cardiovascular and pulmonary events. Effective pain management may reduce their risk of serious postoperative complication, such as deep vein thrombosis and pulmonary emboli. The objective of this study is to evaluate the efficacy of intraperitoneal local anaesthetic, ropivacaine, to reduce postoperative pain in patients undergoing laparoscopic Roux-en-Y gastric bypass. Methods and analysis: A randomised controlled trial will be conducted to compare intraperitoneal ropivacaine (intervention) versus normal saline (placebo) in 120 adult patients undergoing bariatric bypass surgery. Ropivacaine will be infused over the oesophageal hiatus and throughout the abdomen. Patients in the control arm will undergo the same treatment with normal saline. The primary end point will be postoperative pain at 1, 2 and 4 h postoperatively. Pain measurements will then occur every 4 h for 24 h and every 8 h until discharge. Secondary end points will include opioid use, peak expiratory flow, 6 min walk distance and quality of life assessed in the immediate postoperative period. Intention-to-treat analysis will be used and repeated measures will be analysed using mixed modelling approach. Post-hoc pairwise comparison of the treatment groups at different time points will be carried out using multiple comparisons with adjustment to the type 1 error. Results of the study will inform the feasibility of recruitment and inform sample size of a larger definitive randomised trial to evaluate the effectiveness of intraperitoneal ropivacaine. Ethics and dissemination: This study has been approved by the Ottawa Health Science Network Research Ethics Board and Health Canada in April 2014. The findings of the study will be disseminated through national and international conferences and peer-reviewed journals. Trial registration number: Clinicaltrial.gov NCT02154763 .